Pengaruh Sistem Akuntansi Manajemen dan Strategi Bisnis Terhadap Kinerja Manajerial - Tika Hermawati (Journal of Innovation in Management, Accounting and Business, 2023)
A company leader must be able to improve his managerial performance, so that the company he leads can have high performance. Aspects that can affect managerial performance include management accounting systems and good business strategies. This study aims to determine the effect of management accounting systems and business strategy on managerial performance. The focus of this research is management accounting systems, business strategy and managerial performance. The research method used is descriptive verification. This research was conducted at Citradream Hotel Cirebon with a sample of 33 hotel employees. Data was collected using a questionnaire and analyzed using multiple regression. Based on the research results, it was found that there was a significant influence of business strategy and management accounting systems on managerial performance at Citradream Hotel Cirebon, either partially or simultaneously. The contribution made by business strategy and management accounting systems to managerial performance at Citradream Hotel Cirebon is 61.7%. The conclusion from this study is that the management accounting system and business strategy affect managerial performance.